2019
DOI: 10.1021/acs.jafc.9b04949
|View full text |Cite|
|
Sign up to set email alerts
|

Application of a Plant Biostimulant To Improve Maize (Zea mays) Tolerance to Metolachlor

Abstract: Plant biostimulants (PBS) increase crop productivity and induce beneficial processes in plants. Although PBS can stimulate plant tolerance to some abiotic stresses, their effect in improving crop resistance to herbicide injuries has barely been investigated. Therefore, a study on the effect of a biostimulant (Megafol) on maize (Zea mays L.) tolerance to a chloro-acetanilide herbicide (metolachlor) was carried out. We found that Megafol reduced the negative effects of metolachlor on maize. Indeed, biostimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…MDA is a lipid peroxidation product that accumulates in oxidative perturbations, even though it is commonly produced in mitochondria and chloroplasts, where metabolic processes characterized by high electron flow occur [6,29]. The results of our study evidenced that salinity decisively increased the amount of MDA when maize was treated with NaCl alone (Figure 2B), but it decreased when the samples were biostimulated.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…MDA is a lipid peroxidation product that accumulates in oxidative perturbations, even though it is commonly produced in mitochondria and chloroplasts, where metabolic processes characterized by high electron flow occur [6,29]. The results of our study evidenced that salinity decisively increased the amount of MDA when maize was treated with NaCl alone (Figure 2B), but it decreased when the samples were biostimulated.…”
Section: Discussionmentioning
confidence: 59%
“…The MDA content was determined in maize shoots (0.5 g FW) which were extracted in a solution containing 10% (w/v) trichloroacetic acid and 0.25% (w/v) thiobarbituric. The suspension was then centrifuged for 20 min at 10,000× g [29]. After that, the MDA content was determined spectrophotometrically at 532 and 600 nm and referred to the samples' FW.…”
Section: Hydrogen Peroxide (H 2 O 2 ) and Malondialdehyde (Mda) Contentsmentioning
confidence: 99%
“…When produced in high quantities, MDA is itself toxic to the cell. Increases in MDA content have been correlated with oxidative damage due to biotic and abiotic stresses [ 37 , 57 ]. In this context, our results indicate that zinc NPs led to a general reduction in MDA.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatants were heated in a water bath (95 °C). After quick cooling, the MDA content was quantified spectrophotometrically [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The MDA content can reflect the degree of damage to the plant cell membrane and ROS. Under herbicide stress, the MDA content of maize (Panfili et al, 2019), wheat (Bao, 2020), and soybean (Li et al, 2020) was significantly increased. These results showed a significant increase in MDA concentration of foxtail millet under ≥30 g ai ha −1 pyrazosulfuron-methyl treatment, which indicated that the cell integrity of the foxtail millet leaves was compromised; however, with the progress of the fertility process, pyrazosulfuron-methyl at low doses (≤60 g ai ha −1 ) had a certain degree of relief on membrane damage, while there was no obvious recovery under 120 g ai ha −1 pyrazosulfuron-methyl treatment.…”
Section: Discussionmentioning
confidence: 99%